SALARY, WAGE, AND HONORARIUM IN THE FOUNDATION VIEWED FROM THE LAW OF THE FOUNDATION AND THE AUDITOR'S VIEW - Al Kautsar, Mohammad Yudithama (Fakultas Agama Islam Universitas Islam As Syafi'iyah, 2023)
The Foundation is a non-profit legal entity that is widely established in Indonesia, engaged in social and community fields. Foundations get funding from community donations depending on what field the Foundation is engaged in. Foundations in Indonesia are easy to get donations, supported by the Indonesian people who are known to be very generous, this makes Foundations prone to fraud and violations of the law. One of the things that need to be considered in the management of the Foundation is that there is a strict prohibition in the Foundation Law that the Founders and Organs of the Foundation are prohibited from receiving salaries, wages, or honorariums, even the prohibition is threatened with criminal threats. In its activities, Foundations with the receipt of donations or certain amounts of assets are required to have their financial statements audited, and some Foundations have done so. In the audit of financial statements, the auditor uses auditing standards and one of the standards is SA 250 regarding consideration of laws and regulations in the audit of financial statements. When there is a violation of Article 5 of the Foundation Law, the auditor must act as required by Auditing Standard SA 250, and there are different ways of assessing from the law enforcement side of the Foundation Law and from the auditor's point of view of the violation. This paper is different from previous writings which only look at the provision of salaries, wages, and honoraria from a legal perspective, while in this paper it is associated with auditing standards and the code of ethics of the public accounting profession, where the code of ethics regulates considerations of non-compliance with laws and regulations. new client set in Year 2020.